Exploring the lived and coping experiences of patients with kidney failure undergoing haemodialysis in Malaysian private hospitals - Woei Ling, Tan; Khuan, Lee; Baharom, Anisah; Arshad, Mohd Mursyid (SAGE Publications, 2024)
Background: Chronic kidney disease is associated with structural and functional abnormalities in the kidney caused by a range of different aetiologies. Purpose: The study’s purpose was to explore the lived and coping experiences of patients with kidney failure undergoing haemodialysis in three private hospitals in Malaysia. Methods: Applying an interpretative phenomenological analysis using a hermeneutic phenomenological design to derive common meaning from participants lived and coping experiences. In the study, data were collected using a semi-structured interview guide from 15 purposefully sampled patients with kidney failure. Data were analysed using the interpretative phenomenological analysis principles. Results: Patients with kidney failure reported emotional distress, life limitations, financial burdens, knowledge deficits and varying perceptions of the haemodialysis treatment. Body image changes, financial assistance, social support and hope were coping strategies used by patients with kidney failure. It was identified that patients with kidney failure used unique coping strategies such as applying perfume and using clothes to conceal the impact of haemodialysis on their bodies, which is not comprehensively discussed in published literature. Conclusion: Nurses who deliver care to patients with kidney failure should focus on mitigating emotional distress, increasing knowledge related to kidney failure and improving perception of the haemodialysis treatment. Delivering and providing social support are indispensable nursing roles to help patients cope with haemodialysis treatment.